Uma análise no feminino artes e ofícios de cura: benzedeiras e parteiras de Ituiutaba 1950/2006 - Borges, Rosane Ribeiro (2007)
I expose the specificities of the feminine world, searching the women quacks and obstetricians in Ituiutaba-MG, between 1950 and 2006. I discuss the process of individuality of these women socially configured, whose labors and arts of cure sustain traditions and customs which moves in the flexible texture social and are presented through the Social History Theory. Practical the feminine ones of cure are expressions of the popular treatment forms of the most varied evils. Thus, I elaborate an understanding of the daily one lived deeply by the women whom protect and cure, a social manifestation of the express gift in the work to bless and to be midwife.